Assessing routine childhood vaccination acceptance, hesitancy and refusal in Cape Town, Western Cape, South Africa: a mixed-method study protocol - Charles Shey Wiysonge; Lindi Mathebula; Moleen Zunza; Sara Cooper (BMJ Open)
Introduction Vaccines have proven to be one of the most effective ways to prevent infections. Since the introduction of the Expanded Programme on Immunisation worldwide by WHO in 1974, vaccines have saved more than 150 million lives and prevented countless illnesses and disabilities. In South Africa, vaccination has contributed substantially to the decline in under-five childhood deaths from 89 418 in 2005 to 47 409 in 2013. However, the country still has limitations in achieving optimal uptake of vaccines.Methods This study will use a mixed-methods design to identify the factors associated with acceptance, hesitancy and refusal of childhood vaccines in three subdistricts of the Cape Town Metropolitan Health District in South Africa. In phase I of the study, we aim to estimate the uptake of childhood vaccines and assess the factors associated with uptake among a representative sample of at least 236 caregivers of children aged 0–2 years in a cross-sectional study. For phase II of the study, we will explore the behavioural and social drivers of childhood vaccination from the perspective of caregivers of children aged 0–2 years using a purposively selected sample of 20–25 participants from phase I. Finally, for phase III of the study, we will explore the behavioural and social drivers of childhood vaccination from the perspective of 20–25 healthcare workers providing vaccinations to children aged 0–2 years purposively sampled from primary healthcare facilities.Ethics and dissemination Ethical approval was obtained from Stellenbosch University (S23/10/232). Various steps will be taken to ensure the anonymity and confidentiality of participants. Findings of the study will be shared with various healthcare stakeholders through conferences and presentations at relevant meetings.Conclusion Evidence from several studies conducted in South Africa shows a significant increase in vaccine hesitancy within the country. The findings of this study will provide insight into the characteristics associated with vaccine acceptance, hesitancy and refusal in Cape Town. The results will help inform the development of evidence-based interventions that can be implemented to improve vaccination coverage.